2021
DOI: 10.21123/bsj.2021.18.3.0455
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Screening and Antibiotic Sensitivity of Pseudomonas species from Kelana Jaya Lake Soil in Selangor Malaysia

Abstract: Pathogenic microorganisms from hospitals, communities, and the environment remain great threats to human health. The increasing concern about antibiotic resistance has also necessitated the search for robust alternatives. Therefore, this study aims to isolate, screen and evaluate the antibiotic susceptibility of Pseudomonas aeruginosa isolated from a soil sample taken from northern, western and eastern parts of Kelana Jaya Lake against four antibiotics (gentamycin, tetracycline, ampicillin, and penicillin) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In several articles, in-depth research identified specific chemicals in cell-free supernatants that have anti-QS activity 17 or alter the surface characteristics of bacterial cells 18 . On the other hand, the use of microorganisms in the field of biotechnology is one of the most prominent scientific developments used to protect economically and medically important plants from pathogens of all kinds 19 , and in this context, many bacterial species were used, including the genus Pseudomonas, mainly isolated from the soil , where it is located near the roots of plants and releases metabolites that promote plant growth and prevent the activity of pathogenic microbes 20,21 . As well as its positive effect in reducing the levels of toxic chemicals and heavy metals in the soil 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In several articles, in-depth research identified specific chemicals in cell-free supernatants that have anti-QS activity 17 or alter the surface characteristics of bacterial cells 18 . On the other hand, the use of microorganisms in the field of biotechnology is one of the most prominent scientific developments used to protect economically and medically important plants from pathogens of all kinds 19 , and in this context, many bacterial species were used, including the genus Pseudomonas, mainly isolated from the soil , where it is located near the roots of plants and releases metabolites that promote plant growth and prevent the activity of pathogenic microbes 20,21 . As well as its positive effect in reducing the levels of toxic chemicals and heavy metals in the soil 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa is responsible for about 10% of all nosocomial bacterial infections, and as a result, 25-60% of patients pass away (Kumar, Paliya, & Singh, 2022). In terms of antibiotic resistance, the genus Pseudomonas is diverse and one of the most virulent pathogens (Ahmed, Aljondi, Alabed, Al-Mahdi, & Abdsalam, 2021). In roughly 65% of infections, bacteria develop as biofilms, which attach to and spread across the surface of plants (roots) or animals (epithelium).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, P. aeruginosa is an opportunistic pathogen responsible for serious infections 3 . It is the major bacterial pathogen that colonizes cystic fibrosis patients and is one of the most common infectious agents in nosocomial infections, along with severe burn, cancer, transplantation and acquired immunodeficiency syndrome(AIDS) 4 .Also in the hospital, it is responsible for the formation of biofilms on the medical device surfaces 5 .Several virulence factors may cause its pathogenicity 6 , one example is the presence of lipopolysaccharide (LPS).The LPS is the primary element of the outer surface of P. aeruginosa that creates biofilm. A 2024, 21 (2): 0313-0327 https://doi.org /10.21123/bsj.2023.7709 P-ISSN: 2078-8665 -E-ISSN: 2411 Baghdad Science Journal biofilm is a collection of microorganisms that are enclosed in extracellular polymeric substances, which are made up of proteins, polysaccharides, and extracellular DNA 7 .…”
Section: Introductionmentioning
confidence: 99%